Community-based instructional strategies, school location, and primary school pupils’ environmental knowledge (2015)
The environmental issues we face as individuals and as a society are pervasive and ingrained in our cultural ways of being so that we can no longer look to science and technology to solve these problems alone. Instead, educators have been charged with providing students with environmental education through community-based service learning and educational trips. This study investigated the effects of these two community-based instructional modes relative to traditional instruction and any moderating effect of school location on primary school pupils’ environmental knowledge in Oyo Metropolis, Nigeria. The study adopted a pretest-posttest quasi-experimental design. The Environmental Knowledge Test was used to elicit responses from 264 primary-5 pupils across 12 schools. There was a significant main effect of instruction on pupils’ environmental knowledge and significant interaction effect of treatment and school location. This suggests that curriculum developers and planners should promote service learning and educational trips for effective teaching and learning of social studies.